Maternal mortality in Greater São Paulo: an ecological study from 2021 to 2023 (Revista Científica Integrada, 2025)
Objective: To analyze the factors associated with maternal mortality in Greater São Paulo, based on the variables of ethnicity, education level, and age group. Method: This is a descriptive ecological study using secondary data from the TabNet platform of DataSUS, with information from the Mortality Information System (SIM) and the Live Birth Information System (SINASC), covering the period from 2021 to 2023. The variables analyzed were ethnicity, educational attainment, and age group of women who died. Statistical analysis was performed using Jamovi software (version 2.3), applying the Chi-Square (χ²) test for independent samples, with a significance level set at p < 0.01. Results: A downward trend in maternal mortality was observed over the analyzed period, with a rate of 70.51 per 100,000 live births in 2021, decreasing to 43.75 in 2023. Conclusion: The predominant profile of maternal deaths in Greater São Paulo consisted of women who were of mixed race (parda), aged between 30 and 39 years, and had 8 to 11 years of schooling, corresponding to incomplete secondary education.
Keywords: Maternal Mortality; Health Inequities; Risk Factors.